2022
DOI: 10.1038/s41467-022-34739-y
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR endonuclease gene drive reveals distinct mechanisms of inheritance bias

Abstract: CRISPR/Cas gene drives can bias transgene inheritance through different mechanisms. Homing drives are designed to replace a wild-type allele with a copy of a drive element on the homologous chromosome. In Aedes aegypti, the sex-determining locus is closely linked to the white gene, which was previously used as a target for a homing drive element (wGDe). Here, through an analysis using this linkage we show that in males inheritance bias of wGDe did not occur by homing, rather through increased propagation of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Similar to what we observed at the white locus, previous studies in Ae. aegypti 25 also showed that the biased inheritance observed has both a meiotic drive and a homing component. Interestingly, while the vast majority of components tested in that previous Ae.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Similar to what we observed at the white locus, previous studies in Ae. aegypti 25 also showed that the biased inheritance observed has both a meiotic drive and a homing component. Interestingly, while the vast majority of components tested in that previous Ae.…”
Section: Discussionmentioning
confidence: 92%
“…It could have negatively impacted the homing-based biased inheritance of the white-gRNA6 construct, similar to previous observations in Ae. aegypti 24,25 . We employed a marked-chromosome strategy to identify homing events at the white locus that con rmed this is occurring and that an additional contributing effect also enhances the biased inheritance, likely a meiotic drive component destroying some of the receiver chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, molecular tools, such as broadly neutralizing antibodies 5 and encoded miRNA arrays 6,7 have been demonstrated to mitigate DENV and ZIKV transmission by mosquitoes. Additionally, CRISPR-Cas technologies have been engineered to control mosquito populations using the precision-guided Sterile Insect Technique (pgSIT) 8 and confinable gene drives 9,10 . These molecular tools present great promise as vector control strategies capable of reducing viral spread by mosquitoes.…”
Section: Introductionmentioning
confidence: 99%